12‐O‐tetradecanoylphorbol‐13‐acetate and EZH2 inhibition: A novel approach for promoting myogenic differentiation in embryonal rhabdomyosarcoma cells. Issue 3 (30th August 2017) - Marchesi, Irene; Sanna, Luca; Fais, Milena; Fiorentino, Francesco P.; Giordano, Antonio; Bagella, Luigi
Abstract : Rhabdomyosarcoma (RMS) is a soft tissue sarcoma that arises from muscle precursors affecting predominately children and young adults. It can be divided into two main classes: embryonal (eRMS) and alveolar rhabodomyosarcomas (aRMS). Despite the expression of early muscle specific genes, RMS cells fail to complete myogenesis even in differentiation conditions. We previously demonstrated that Enhancer Zeste of Homolog 2 (EZH2), the catalytic subunits of PRC2 complex, contributes to inhibit muscle differentiation in eRMS and its down‐regulation causes a partial recovery of myogenesis. 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) is a molecule able to induce differentiation in eRMS with a mechanism that involves the protein kinase C (PKC). In this paper we report that treatment with TPA reduces the expression of EZH2 without affecting levels of H3K27me3. The combination of TPA with GSK126, an inhibitor of the catalytic activity of EZH2, has a synergic effect on the induction of muscle differentiation in RD rhabdomyosarcoma cells, suggesting a new therapeutic combinatory approach for RMS treatment. Abstract : Rhabdomyosarcoma (RMS) is a soft tissue sarcoma that arises from muscle precursors. We previously demonstrated that down‐regulation of EZH2 in RMS cells causes a partial recovery of myogenesis. We report that the combination of TPA with GSK126 scores a synergic effect on the induction of muscle differentiation, suggesting a new therapeutic combinatory approach for RMS treatment